Choline rise in the rat hippocampus induced by electroconvulsive shock treatment - Sartorius, Alexander; Neumann-Haefelin, Claudia; Vollmayr, Barbara; Hoehn, Mathias; Henn, Fritz A. (Biological psychiatry, 2003)
Background - Human hippocampal choline decreases in major depression episodes. This decrease was recently measured by 1H magnetic resonance spectroscopy (MRS), and it has been found that its level normalizes during antidepressive electroconvulsive therapy. We hypothesized a hippocampal choline increase in the rat brain under electroconvulsive shock (ECS) treatment. - Methods - Rat hippocampi (n = 28) were investigated via magnetic resonance spectroscopy and signal intensities of choline (Cho), total creatine (tCr), and N-acetyl aspartate (NAA) were measured and expressed as ratios before and after six ECS treatments. - Results - After ECS treatment, hippocampal choline increases significantly: Cho/tCr ratio: +13% and Cho/NAA ratio: +19% increase. - Conclusions - We found a rise of relative choline concentration induced by ECS treatment in rat hippocampus measured in vivo with magnetic resonance spectroscopy. This increase corresponds to the increase of choline in human hippocampus after electroconvulsive shock treatment. Because choline measured via 1H-spectroscopy is believed to represent primarily phosphocholine and glycerophosphocholine, and therefore phospholipase A2 activity and membrane turnover, our results are in good agreement with reported ECS-induced hippocampal mossy fiber sprouting, increased synaptic plasticity, and neurogenesis.
Gesehen am 05.11.2020